Rate constants and kinetic isotope effects for H-atom abstraction reactions by muonium in the Mu + propane and Mu + n-butane reactions from 300 K to 435 K: challenges for theory. Issue 11 (5th March 2020) - Fleming, Donald G.; Arseneau, Donald J.; Cottrell, Stephen P.; Peck, Jamie N. T.
Abstract : This paper reports measurements of the temperature dependence of the rate constants for H-atom abstraction reactions from propane and n -butane by the light isotopic H-atom muonium (Mu), k Mu ( T ), over temperatures in the range 300 K to 435 K. Abstract : This paper reports measurements of the temperature dependence of the rate constants for H-atom abstraction reactions from propane and n -butane by the light isotopic H-atom muonium (Mu), k Mu ( T ), over temperatures in the range 300 K to 435 K. Simple Arrhenius fits to these data yield activation energies, E Mua, that are some 2–4 times lower than E Ha found from corresponding fits for the H + propane and H + n -butane reactions studied elsewhere, both experimentally and theoretically, and fit over a similar temperature range. These activation energies E Mua are also much lower than estimated from zero-point-energy corrected vibrationally adiabatic potential barriers, both results suggesting that quantum tunneling plays an important role in determining k Mu ( T ) and for the Mu + propane reaction in particular. The results are expected to pose a considerable challenge to reaction rate theory for isotopic H-atom reactions in alkane systems.